Special Issue “Urban and Buildings Regeneration Strategy to Climatic Change Mitigation, Energy, and Social Poverty after a World Health and Economic Global Crisis” - Pilar Mercader-Moyano (MDPI AG, 2021)
Throughout the 21st century, urban reports demand solutions to the obsolescence and aging process suffered by the existing buildings, due to the growth and expansion of cities that took place in the second half of the 20th century [...]